Diosmetin protects against retinal injury via reduction of DNA damage and oxidative stress. (2016) - Shen, Zeren; Shao, Jinjin; Dai, Jiabin; Lin, Yuchen; Yang, Xiaochun; Ma, Jian; He, Qiaojun; Yang, Bo; Yao, Ke; Luo, Peihua
Abstract: Visual impairment is a global public health problem that needs new candidate drugs. Chrysanthemum is a traditional Chinese drug, famous for its eye-protective function, with an unclear mechanism of action. To determine how chrysanthemum contributes to vision, we identified, for the first time, the component of chrysanthemum, diosmetin (DIO), which acts in protecting the injured retina in an adriamycin (ADR) improving model. We observed that DIO could attenuate the apoptosis of retinal cells in Sprague–Dawley rats and verified this effect in cultured human retinal pigment epithelium (RPE) cells, ARPE-19. Our further study on the mechanism revealed the counteractive effect of DIO on the attenuation of DNA damage and oxidative stress, which occurs in a wide range of retinal disorders. These results collectively promise the potential value of DIO as a retinal-protective agent for disorders that lead to blindness. In addition, we identified, for the first time, the component of chrysanthemum, DIO, which acts in protecting the injured retina.